Navigating Success and Challenges in Arteriovenous Fistulain Pediatrics: A Retrospective Observational Study: Navigating Success in Arteriovenous Fistula - Rajput, Manharsinh; Banerjee, Subho (Journal of Pediatric Nephrology, 2025)
Background and Aim: Arteriovenous fistula (AVF) is an essential surgery for young patients who need long-term access to hemodialysis (HD). Despite the widespread use of AVFs in adult populations, there is a lack of research on their utilization and outcomes in pediatric patients. The purpose of this study was to assess the outcomes of AVF development in children, including the factors that affect success rates, complications, and long-term outcomes. Methods: This study was a retrospective cohort of patients with end-stage renal disease (ESRD) who were aged under 18 years old and underwent an AVF surgery at our center between December 2021 and January 2023. We collected demographic data from patients and follow-up data at 1 week, 6 weeks, 6 months, 12 months, and 18 months. Details, such as the type of access, its anatomical location, and complications, were also documented. Results: During the study period, a total of 47 AVFs were created. We created brachiocephalic AVF in 63.83% of cases (n=30), radiocephalic AVF in 14.89% (n=07), and brachiobasilic transposition in 21.28% (n=10). The overall primary patency rate at 12 months was 78.72%. The median survival of the brachiocephalic fistula was much greater than that of the radiocephalic and brachiobasilic fistulas (BBF). The primary patency rates at 1 week, 6 weeks, 6 months, 12 months, and 18 months were 87.23%, 85.11%, 82.97% and 74.47%, and 66%, respectively. Conclusion: AVF provides effective long-term HD access in the pediatric population with ESRD. Thromosis was identified as the main cause of failure, underscoring the importance of proactive monitoring and interventions to improve outcomes.